Estudio hidrológico de cuencas pareadas mediante métodos de teledetección y modelación matemática. - Maldonado Chávez, Carlos Andrés (2024)
This study analyzes the impact of land-use changes on the hydrological dynamics of the Igualata Páramo, a critical ecosystem for water regulation in the Andean region of Ecuador. The paired watershed method was applied to compare the hydrographic units of Jatunchimbana and Gualcanga, using remote sensing and hydrological modeling with the HEC-HMS model. The results showed that Jatunchimbana, characterized by more significant agricultural intervention, experienced a 15% increase in surface runoff and a 12% decrease in water retention capacity. Conversely, Gualcanga, with predominantly native vegetation cover, maintained an average water yield of 0.4024 m³/s and greater stability in its ecological flows. These differences highlight the negative impact of human activities on hydrological dynamics, in contrast to the benefits of preserving native vegetation cover. The conclusions emphasize the need for sustainable management strategies, such as reforestation with native species and constant monitoring of land use changes, to ensure water sustainability. This work contributes to the design of public policies focused on páramo conservation and mitigating the effects of climate change and anthropogenic pressure on water resources.